En moderniserad genusordning? - En netnografisk studie om reproduktion av könsroller genom talande om maskulina och feminina energier på Tiktok - Ochante Björk,Estella; Widlund,Julia (2025)
This study aimed to investigate whether and in what way gender roles are reproduced through the conversation regarding masculine and feminine energies among Swedish TikTok users. Former research shows that youth's lives increasingly revolve around social media. There are online forums where gendered stereotypes are reproduced and alleged messages are being spread about a decreasing privilege for men. This study was based on a thematic analysis of transcribed videos gathered on TikTok. The data was analyzed with a theoretical framework based on the logic of separation, Hierarchy, and Gender contract. The results show that publishing users on TikTok are making use of masculine and feminine energies to reproduce gender roles. Men and women are constructed as each other's opposites with different traits and commitments through the logic of separation. Men are placed in a higher hierarchical position by being given the right to make decisions and take action, while women are placed in a subordinate position by being expected to adjust accordingly. In conclusion, we observe that masculine and feminine energies are being used by Swedish Tiktokers to form a new gender order.
Keywords: masculine energy; feminine energy; gender roles; tiktok; Gender order; maskulin energi; feminin energi; könsroller; genusordning